2020
DOI: 10.1155/2020/3520856
|View full text |Cite
|
Sign up to set email alerts
|

Management of Cataract in Patients with Irregular Astigmatism with Regular Central Component by Phacoemulsification Combined with Toric Intraocular Lens Implantation

Abstract: Purpose. To evaluate visual acuity (VA) and refractive status in patients with cataract and irregular astigmatism with a regular central component after phacoemulsification with implantation of a toric intraocular lens (IOL). Methods. Patients with cataract associated with irregular astigmatism with a regular central component were enrolled. All patients underwent phacoemulsification and toric IOL implantation. Postoperative visual acuity, residual astigmatism, toric IOL rotation, higher-order aberration, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…The incidence of RA >1.00 DC, after implanting toric IOL without considering measured BSA in the calculation of IOL power, is about 20% [ 11 , 12 ]. Gao et al [ 12 ] employed a fixed FCA/BCA ratio constant to further refine their estimates for IOL powers, but this did not nullify the incidence of postoperative refractive surprises. Bandeira et al [ 11 ] used Orbscan II to measure corneal front surface astigmatism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of RA >1.00 DC, after implanting toric IOL without considering measured BSA in the calculation of IOL power, is about 20% [ 11 , 12 ]. Gao et al [ 12 ] employed a fixed FCA/BCA ratio constant to further refine their estimates for IOL powers, but this did not nullify the incidence of postoperative refractive surprises. Bandeira et al [ 11 ] used Orbscan II to measure corneal front surface astigmatism.…”
Section: Discussionmentioning
confidence: 99%
“…Ignoring corneal back surface astigmatism can lead to errors in estimating the surgically induced astigmatism and IOL power selection [1][2][3][4][5][6][7][8][9][10]. Two recent studies found that ocular residual astigmatism >1.00 DC occurred in approximately 20% of eyes at 3 months postoperatively [11,12]. ese two investigations were based on quite different patient groups, toric IOL designs, surgical procedures, and IOL power algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…However, sometimes patients with irregular astigmatism (this is an off-label use) also benefit from these lenses. [ 38 39 ] Since these patients often have high astigmatism, use of customized IOLs have resulted in a significant reduction of astigmatism with good outcomes. [ 40 ] Post-penetrating keratoplasty: post-keratoplasty patients often have early cataract formation due to prolonged use of steroids and also have high astigmatism due to irregular healing of the graft host junction.…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…However, sometimes patients with irregular astigmatism (this is an off-label use) also benefit from these lenses. [ 38 39 ] Since these patients often have high astigmatism, use of customized IOLs have resulted in a significant reduction of astigmatism with good outcomes. [ 40 ]…”
Section: Indications and Contraindicationsmentioning
confidence: 99%
“…10 In addition, corneal back surface astigmatism is claimed to impact on the performance of the eye in relation to refractive surgery 11,12 and planning for cataract surgery especially in astigmatic eyes. [13][14][15][16][17][18][19][20][21][22][23][24][25] Some investigators reported that corneal back surface astigmatism remains stable after refractive surgery, and this would have a marginal impact on later routine phacoemulsification. [26][27][28][29][30][31][32] This is certainly not the case in patients that underwent more invasive procedures, such as radial keratotomy, where profound changes in corneal back surface astigmatism can occur.…”
Section: Introductionmentioning
confidence: 99%